Homogeneous Distribution of Carbon Nanotubes in Copper Matrix Nanocomposites Fabricated via Combined Technique - ., Ali Samer Muhsan, Faiz Ahmad, Norani M. Mohamed, Puteri Sri Melo (2014)
Carbon nanotubes (CNTs) with its exceptional thermal and mechanical properties hold the promise of delivering high performance nanocomposite materials. To utilize CNTs as effective reinforcement in metal nanocomposites, appropriate dispersion and robust interfacial adhesion between individual CNT and metal matrix have to be certain. This work presents a novel combined technique of nanoscale dispersion (NSD) of functionalized multiwalled carbon nanotubes (MWCNTs) in copper (Cu) matrix composite followed by powder injection molding (PIM). MWCNTs contents were varied from 0 to 10 volume fraction. Evidences on the existence of functional groups and microstructural analysis of the fabricated nanocomposites were determined using TEM, EDX, FESEM and FTIR. Thermal conductivity and elasticity measurements were also performed. The results showed that the impurities of the pristine MWCNTs such as Fe, Ni catalyst, and the amorphous carbon have been significantly removed after sonication process. FESEM and TEM observations showed high stability of MWCNTs at elevated temperatures and uniform dispersion of MWCNTs in Cu matrix at different volume fractions and sintering temperatures (950, 1000 and 1050 C). The experimentally measured thermal conductivities of Cu/MWCNTs nanocomposites showed remarkable increase (11.25% higher than pure sintered Cu) with addition of 1 vol.% MWCNTs, while the modulus of elasticity (Young's modulus) of Cu/MWCNTs nanocomposites sintered at 1050 °C for 2 h was increased proportionally to the increment in MWCNTs contents.